A Retrospective Observational Drug Utilization Study on COVID-19 At Tertiary Care Teaching Hospital (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The Coronavirus Disease 2019 (COVID-19) pandemic has presented an unparalleled challenge to healthcaresystems worldwide since its emergence in late 2019. As health-care providers grapple with the complexities ofmanaging COVID-19 patients, the need for comprehensive understanding of treatment strategies and drug utilizationpatterns becomes increasingly critical. In response to the evolving nature of the pandemic, health-care facilities haveimplemented various therapeutic interventions, often adapting treatments based on emerging evidence and clinicalexperience. This manuscript presents a retrospective observational drug utilization study conducted at a tertiary careteaching hospital, aimed at examining the patterns of drug utilization among COVID-19 patients. With the rapiddevelopment and dissemination of treatment guidelines and protocols, understanding real-world drug utilizationpatterns is essential for optimizing therapeutic approaches and informing evidence-based clinical decision-making.Ultimately, this research aims to contribute to the collective efforts to mitigate the impact of the COVID-19 pandemicand improve outcomes for patients receiving care at tertiary care teaching hospitals. Objective: The objective of thestudy is to analyze prescribing patterns in COVID-19 patients and to find the prevalence of co-morbidities associatedwith COVID-19. Methods: A total of 500 patients diagnosed with COVID-19 were finally recruited after strictlyobeying the selection criteria in this retrospective, observational study conducted over 6 months in a tertiary careteaching hospital, Parul Sevashram Hospital. Relevant data were extracted from prescriptions, case records, andinvestigational reports. Results: Of the total 500 patients, 300 (60%) were males and 200 (40%) females. The highestnumbers of patients were in the age group of 46–55 years (147 patients, 29.34%). Out of 500, 289 patients hadcomorbidity in which hypertension was the most common comorbidity (115 patients, 39.8%) observed, followed bydiabetes (102 patients, 35.3%) and diabetes mellitus plus hypertension (52 patients, 18%). Commonly employed intreatment were class of medications such as anticoagulant (9.3%), antipyretic (8.7%), folic acid supplements (8.4%),Vitamin C supplements (8.4%), proton pump inhibitors (8.3%), Vitamin D supplements (8.1%), steroids (7.7%), andantibiotics (7.6%), while other classes of drugs such as anthelmintics, antitussive, antiviral, and antihypertensive wereadministered according to the patient’s specific disease state and the severity of their condition. Conclusion: Furtherinvestigation is warranted on the evolving subject of COVID-19 due to the virus’s variability and characteristics,alongside the insufficient evidence backing current treatment drugs for the development of updated guidelines,ultimately lessening the strain on global health-care providers. Future research endeavors will focus on refiningdrug utilization and prescription practices for COVID-19 treatment. Regular evaluation of drug utilization patterns isimperative for enhancing management strategies and the overall quality of life for patients.